Creating customer value through industrial services : case: Raute Technology Services - Lakka, Eveliina (2014)
The role of marketing can be seen as to assist the company on creating superior value for its customers, so that they would succeed against their competitors. Creating superior value has not always been essential, as in the past firms could achieve profitability due to regulated markets, controlled distribution channels or scarce resources. An increasing number of industrial manufacturing companies are moving from offering solely products to offering combinations of products and services. Customers benefit from industrial services as they support and enable the value generation of the products they have purchased. To firms, offering services is a matter of competitive advantage since services are harder to copy and easier to customize, due to their intangibility and heterogeneous nature.